2022
DOI: 10.3390/su14042312
|View full text |Cite
|
Sign up to set email alerts
|

The Bridge at the End of the World: Linking Expat’s Pandemic Fatigue, Travel FOMO, Destination Crisis Marketing, and Vaxication for “Greatest of All Trips”

Abstract: The rebirth of global tourism with a massive rebound is anticipated due to an emerging touristic behavior coined as vaxication (i.e., post-vaccination travel). Despite the ongoing fatigue triggered by the COVID-19 pandemic, travelers’ fear of missing out (FOMO), and destination crisis marketing (DCM) can further accelerate travelers’ momentum towards vaxication. To address this critical knowledge gap in COVID-19 tourism, the present study aimed to examine the effect of pandemic fatigue on vaxication intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…MacIntyre et al examined the presence of pandemic fatigue by comparing changes in the number of infection prevention measures taken by participants during two specific periods and found that participants' infection pandemic prevention and control practices consistently decreased, indicating pandemic fatigue ( 17 ). Although some scholars have tried to quantify pandemic fatigue, few studies have developed and used specific tools to assess public pandemic fatigue ( 18 ). In addition, studies on pandemic fatigue in China have been scarce, and the development and usage of local measurement tools are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…MacIntyre et al examined the presence of pandemic fatigue by comparing changes in the number of infection prevention measures taken by participants during two specific periods and found that participants' infection pandemic prevention and control practices consistently decreased, indicating pandemic fatigue ( 17 ). Although some scholars have tried to quantify pandemic fatigue, few studies have developed and used specific tools to assess public pandemic fatigue ( 18 ). In addition, studies on pandemic fatigue in China have been scarce, and the development and usage of local measurement tools are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…They are also more discerning about tourism information and its dissemination and are prone to be more skeptical about its accuracy (Pennycook et al ., 2020). It has been argued that the use of social media influencers and celebrity endorsements of destination safety might help to eliminate the sense of fear in the minds of consumers (Zaman et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, pandemic fatigue can most parsimoniously be explained under the cognitive load theory framework. Specifically, the introduction of new ways of performing routine tasks, the rapidly shifting conditions of the pandemic and the uncertainty about the duration of health measures required additional mental resources to process and contributed to overall stress levels 35 .…”
Section: Introductionmentioning
confidence: 99%